2009
DOI: 10.1086/598987
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Superinfection in an HIV‐2–Infected Woman with Subsequent Control of HIV‐1 Plasma Viremia

Abstract: A human immunodeficiency virus type 2 (HIV-2)-infected woman experienced asymptomatic superinfection with HIV-1 subtype AG. She did not have cross-neutralizing autologous HIV-1 antibodies before and shortly after HIV-1 superinfection. This evidence supports a mechanism other than cross-neutralizing antibodies for the mild course of HIV-1 infection in this woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…The first documented cases of HIV superinfection were found in individuals with various modes of transmission and included inter-and intrasubtype cases (1,9,17). Subsequently, multiple studies have documented superinfection in small populations of high-risk individuals (2,3,7,8,11,13,17,20,22,23,26,29). The rate of HIV superinfection in these high-risk groups was relatively frequent and was comparable to the incidence rate in similar populations from the same regions, especially if multiple viral genes were examined (3,13,14,21,24).…”
mentioning
confidence: 99%
“…The first documented cases of HIV superinfection were found in individuals with various modes of transmission and included inter-and intrasubtype cases (1,9,17). Subsequently, multiple studies have documented superinfection in small populations of high-risk individuals (2,3,7,8,11,13,17,20,22,23,26,29). The rate of HIV superinfection in these high-risk groups was relatively frequent and was comparable to the incidence rate in similar populations from the same regions, especially if multiple viral genes were examined (3,13,14,21,24).…”
mentioning
confidence: 99%
“…Still, HIV-2 infection may have mitigated the consequences of HIV-1 infection. Indeed, it has been reported that HIV-1 plasma viremia may be controlled following superinfection in an HIV-2-infected woman (21).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-2 is rare outside of West Africa, Mozambique, Angola and southwest India. A few people might be coinfected with both viruses, and HIV-2 does not induce immunity to prevent HIV-1 superinfection, nor vice versa [10]; doubly infected patients develop an immunodeficiency and all the signs of AIDS earlier. Until now, a recombinant virus composed of parts of HIV-1 and HIV-2 has not been found in humans.…”
Section: Origin Of the Types And Groups Of Hiv And Its Epidemiologymentioning
confidence: 99%